Control of Struvite (MgNH4 PO4 .6H2O) Scale Deposit in an Industrial Process - Luluk Edahwati; Sutiyono; Radissa Dzaky Issafira; Ndaru Adyono; Wiliandi Saputro; Wahyu Dwi Lestari; Ahmad Khairul Faizin; Tria Puspa Sari (Nusantara Science and Technology Proceedings)
Struvite or Magnesium Ammonium Phosphate Hexahydrate (MgNH4 PO4.6H2O) is one of the precipitates generally formed in the piping system. The formation of struvite in the piping system is one of the serious problems that can cause blockages, reduced flow volume, and pipe diameter to increase maintenance and production costs. This formation of struvite scale in the industrial instrument is detrimental; however, struvite can be used as raw material for slow-release fertilizers. This study will observe the effect of pH in the range of 8, 8.5, 9, 9.5, and 10 on the formation of struvite compositions, consisting of Mg, NH4, PO4, Ca, and K in the surrounding temperature of 35oC. The results of this study will be observed using visual MINTEQ software. The result shows that the most suitable pH for struvite formation is 9.5.